Menguasai Ketidakpastian: Strategi dan Keterampilan Membentuk Pembelajaran Masa Kini - Sevtriani, Melanny; Asbari, Masduki; Amaria, Laila; Muhammad, Banginda; Maulana, Akbar (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to understand how to Master Uncertainty to shape modern learners. In this research report, a qualitative descriptive method is used, with data sourced from listening to the spoken narrative on Gita Wirjawan's YouTube channel titled "Hone 3 Things to Embrace Uncertainty" as presented by Gita Wirjawan. The study's findings explain that the concept of Mastering Uncertainty, particularly Heisenberg's Uncertainty Principle, forms the fundamental foundation of quantum physics, distinguishing it from classical physics. Heisenberg's Uncertainty Principle sets limits on the absolute precision of measurements in quantum physics. The design of education aims to prepare students to face future challenges, prioritizing student-centered learning over their desires. The development of emotions, cognitive skills, and character is emphasized with the goal of creating an innovative and beneficial generation for society.